3D VIEW: Designing of a Deception from Distorted View-dependent Images and Explaining interaction with virtual World - Syed Muhammad Ali; Zeeshan Mahmood; Dr. Tahir Qadri (Sir Syed University Research Journal of Engineering and Technology)
This paper presents an intuitive and interactive computer simulated augmented reality interface that gives the illusion of a 3D immersive environment. The projector displays a rendered virtual scene on a flat 2D surface (floor or table) based on the user’s viewpoint to create a head coupled perspective. The projected image is view-dependent which changes and deforms relative to user’s position in space. The nature of perspective projection is distorted and anamorphic such that the deformations in the image give an illusion of a virtual three dimensional holographic scene in which the objects are popping out or floating above the projection plane like real 3D objects. Also, the user can manipulate and interact with 3D objects in a virtual environment by controlling the position and orientation of 3D models, interacting with GUI incorporated in virtual scene and can view, move, manipulate and observe the details of objects from any angle naturally by using his hands. The head and hand tracking is achieved by a low cost 3D depth sensor ‘Kinect’. We describe the implementation of the system in OpenGL and Unity3D game engine. Stereoscopic 3D along with other enhancements are also introduced which further improves the 3D perception. The approach does not require head mounted displays or expensive 3D hologram projectors as it is based on perspective projection technique. Our experiments show the potential of the system providing users a powerful, realistic illusion of 3D.